2017
DOI: 10.1002/app.45416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aggregate size on liquid absorption characteristics of konjac glucomannan superabsorbent

Abstract: In this article, four kinds of konjac glucomannan based superabsorbent polymers (KSAPs) with different aggregate sizes were obtained by sieving the KSAP powders manually. They were characterized by scanning electronic microscopy (SEM), Fourier transform infrared (FTIR), thermogravimetric analysis (TGA), and optical contact angle (OCA), and the effects of aggregate size on liquid absorption characteristics of KSAP were studied in detail. The results show that the coarse KSAP particles were aggregated by many mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
2
1
Order By: Relevance
“…It was deduced that the hydrophilic groups such as COO provided by the PAAS filler make a contribution to the PU foam. This was different from the results of the water absorption studies (Table ): the CA of PUF‐2.6 was the optimum among these four kinds of PAAS/PU composites, a result that might be associated with the uniform cell size and the specific surface area …”
Section: Resultscontrasting
confidence: 91%
“…It was deduced that the hydrophilic groups such as COO provided by the PAAS filler make a contribution to the PU foam. This was different from the results of the water absorption studies (Table ): the CA of PUF‐2.6 was the optimum among these four kinds of PAAS/PU composites, a result that might be associated with the uniform cell size and the specific surface area …”
Section: Resultscontrasting
confidence: 91%
“…The size of superabsorbent polymer particles has been extensively studied to increase their ultimate water absorption capacity. Yang et al found that samples with larger agglomerate sizes had higher water absorption rates, but samples with smaller aggregate sizes took less time to reach water absorption equilibrium [ 139 ]. Arpit Sand [ 140 ] studied the effect of reaction parameters on the water absorption of itaconic acid particles during the synthesis of itaconic acid by reverse suspension polymerization.…”
Section: Forms Of Superabsorbent Polymersmentioning
confidence: 99%
“…less time to reach water absorption equilibrium. [139]. Arpit Sand [140] studied the effect of reaction parameters on the water absorption of itaconic acid particles during the synthesis of itaconic acid by reverse suspension polymerization.…”
Section: Superabsorbent Polymer Particlesmentioning
confidence: 99%